2007
DOI: 10.1080/00140130701217115
|View full text |Cite
|
Sign up to set email alerts
|

Feedback quality and environmentally friendly use of domestic central heating systems

Abstract: The study examined the influence of system-embedded feedback on user behaviour during the environmentally friendly operation of a central heating system. A PC-based simulation, called CHESS, was developed to model the critical features of a central heating system. After having received 30 min of training on the simulation task, 60 participants worked on a series of operational scenarios under different levels of system feedback. In addition to the collection of various performance measures (e.g. energy consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
0
27
1
Order By: Relevance
“…There is other work that also indicates that historical information does not necessarily improve human performance (Palmer et al, 1980). In contrast, in a study providing support to users operating a CHS, it emerged that historical information helped users optimise their system management strategies, resulting in reduced energy consumption (Sauer et al, 2007). The mixed findings from the literature suggest a need for empirical evaluations of the utility of history displays as their effectiveness appears to be dependent on task requirements and situational circumstances.…”
Section: History Displaysmentioning
confidence: 78%
See 3 more Smart Citations
“…There is other work that also indicates that historical information does not necessarily improve human performance (Palmer et al, 1980). In contrast, in a study providing support to users operating a CHS, it emerged that historical information helped users optimise their system management strategies, resulting in reduced energy consumption (Sauer et al, 2007). The mixed findings from the literature suggest a need for empirical evaluations of the utility of history displays as their effectiveness appears to be dependent on task requirements and situational circumstances.…”
Section: History Displaysmentioning
confidence: 78%
“…Research has indicated a number of circumstances under which command displays have provided benefits, such as high time pressure in a decision-making situation (Sarter and Schroeder, 2001). In the context of the CHS operation, there were indications that some users did not have adequate strategies available to manage the system more energyefficiently although they were aware of their undue energy consumption (Sauer et al, 2007). However, there may also be disadvantages associated with the instructional display.…”
Section: Instructional Displaysmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential for computerizing this information system, for exploring different modes of information presentation and decision support, is of obvious relevance, in terms not only of domestic economics but the broader ecological agenda. 1 Designing for the home poses some unique challenges compared to the design of work-based systems (Sauer et al 2007) . This brings us to the second sense of "bound" in the paper's title: the group of users is characterized by a high level of heterogeneity, without the possibility of selection according to technical competence; moreover, no formal training can be given, and users in effect set their own goals and tasks, with no performance supervision, standards, or systematic feedback.…”
Section: Designing For the Homementioning
confidence: 99%